Labor and Politics in Spain Today - Martin, Benjamin (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1979)
The trade unions elections of 1977 in Spain conferred a formal end of four decades of labour authoritarianism and marked the second major electoral process that has been established for the re-establishment of democratic institutions. According to the author, the outcome has important implications for the emerging national political configuration, the restructuring of the labour-management relationship, and the political strategies of the major political parties.